The Effect of Psychological Resilience on Internship Students’ Performance and Job Satisfaction: The Moderating Role of Social Support - Dienullah, Fakhri Akhmad; Palupi, Majang (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of psychological resilience on the performance and job satisfaction of internship program students with social support as a moderating variable. Based on the Conservation of Resources Theory and Social Support Theory, this quantitative study used a Likert scale questionnaire survey of students at the Faculty of Business and Economics, Islamic University of Indonesia. The data were analyzed using simple linear regression and Moderated Regression Analysis (MRA) through SPSS version 26. The results showed that psychological resilience had a positive and significant effect on performance and job satisfaction, while social support strengthened the relationship between the two. These findings confirm that strengthening resilience and social support not only plays a role in improving student performance and job satisfaction during the internship program, but also becomes an important factor in shaping their readiness to face future job challenges.